ANALISIS EFISIENSI PRODUKSI KOPI ROBUSTA DI KABUPATEN TEMANGGUNG - Tri Risandewi (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2013)
This research has the aim and purpose to find out the efficiency of the robusta coffee production, analize the production factors which influence the production of the coffee itself, and get the recommendation in order to improve the efficiency of the coffeee using DEA analysis and regretion in Candiroto District. The efficiency of the average robusta coffee production has not been efficient that is 73,24% . Mento area is the village that has the highest efficiency level and karawitan and Muntung village is the lowest among those villages that we observed. The factors that influence the production in Candiroto District are the width of the land, the workers, the quantity of the plants, the fertilizer, and the age of the plant. The age of the plant is the only variable which is negative toward the production of the robusta coffee. The recommendation for improving the production of the robusta coffee are the people surround the area should limit the unappropriate workers, replanting the coffee plants, reducing the unnecessary fertilizer which can cause infertility of the land, and land intensification.